Losing the dogmatic view of cerebral autoregulation - Brassard, Patrice; Labrecque, Lawrence; Smirl, Jonathan D.; Tymko, Michael M.; Caldwell, Hannah G.; Hoiland, Ryan L.; Lucas, Samuel J. E.; Denault, André Y.; Couture, Etienne J.; Ainslie, Philip N. (Physiological reports, 2021)
In 1959, Niels Lassen illustrated the cerebral autoregulation curve in the classic review article entitled Cerebral Blood Flow and Oxygen Consumption in Man. This concept suggested a relatively broad mean arterial pressure range (~60–150 mmHg) wherein cerebral blood flow remains constant. However, the assumption that this wide cerebral autoregulation plateau could be applied on a within‐individual basis is incorrect and greatly variable between individuals. Indeed, each data point on the autoregulatory curve originated from independent samples of participants and patients and represented interindividual relationships between cerebral blood flow and mean arterial pressure. Nonetheless, this influential concept remains commonly cited and illustrated in various high‐impact publications and medical textbooks, and is frequently taught in medical and science education without appropriate nuances and caveats. Herein, we provide the rationale and additional experimental data supporting the notion we need to lose this dogmatic view of cerebral autoregulation. In 1959, Niels Lassen illustrated the cerebral autoregulation curve in the classic review article entitled Cerebral Blood Flow and Oxygen Consumption in Man. This concept suggested a relatively broad mean arterial pressure range wherein cerebral blood flow remains constant. Herein, we provide the rationale and additional experimental data supporting the notion we need to lose this dogmatic view of cerebral autoregulation.